Роль емпатії в лідерстві - Деркач, К. Ю. (ХНУРЕ, 2025)
In the realm of project management, where deadlines, budgets, and deliverables often dominate the conversation, the role of empathy can sometimes be overlooked. Empathy is one of the key components of effective leadership in the modern world. It helps managers better understand the needs and emotional state of their team, create a trusting atmosphere, and increase productivity. This report discusses the role of empathy in leadership, its impact on corporate culture, employee motivation, and conflict resolution.
Keywords: емпатія в лідерстві; лідерство